Severe delayed hypersensitivity reactions to IL-1 and IL-6 inhibitors link to common HLA-DRB1*15 alleles. Issue 3 (17th November 2021) - Saper, Vivian E; Ombrello, Michael J; Tremoulet, Adriana H; Montero-Martin, Gonzalo; Prahalad, Sampath; Canna, Scott; Shimizu, Chisato; Deutsch, Gail; Tan, Serena Y; Remmers, Elaine F; Monos, Dimitri; Hahn, Timothy; et al.
Abstract : Objectives: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe, delayed hypersensitivity reaction (DHR). We observed DRESS to inhibitors of interleukin 1 (IL-1) or IL-6 in a small group of patients with Still's disease with atypical lung disease. We sought to characterise features of patients with Still's disease with DRESS compared with drug-tolerant Still's controls. We analysed human leucocyte antigen (HLA) alleles for association to inhibitor-related DHR, including in a small Kawasaki disease (KD) cohort. Methods: In a case/control study, we collected a multicentre series of patients with Still's disease with features of inhibitor-related DRESS (n=66) and drug-tolerant Still's controls (n=65). We retrospectively analysed clinical data from all Still's subjects and typed 94/131 for HLA. European Still's-DRESS cases were ancestry matched to International Childhood Arthritis Genetics Consortium paediatric Still's cases (n=550) and compared for HLA allele frequencies. HLA association also was analysed using Still's-DRESS cases (n=64) compared with drug-tolerant Still's controls (n=30). KD subjects (n=19) were similarly studied. Results: Still's-DRESS features included eosinophilia (89%), AST-ALT elevation (75%) and non-evanescent rash (95%; 88% involving face). Macrophage activation syndrome during treatment was frequent in Still's-DRESS (64%) versus drug-tolerant Still's (3%; p=1.2×10 −14 ). We found striking enrichment for HLA-DRB1*15 haplotypes in Still's-DRESS cases versus INCHARGE Still's controls (p=7.5×10 -13 ) and versus self-identified, ancestry-matched Still's controls (p=6.3×10 −10 ). In the KD cohort, DRB1*15:01 was present only in those with suspected anakinra reactions. Conclusions: DRESS-type reactions occur among patients treated with IL-1/IL-6 inhibitors and strongly associate with common HLA-DRB1*15 haplotypes. Consideration of preprescription HLA typing and vigilance for serious reactions to these drugs are warranted.